African Studies Keyword: Democracy. (2nd September 2021) - Cheeseman, Nic; Sishuwa, Sishuwa
Abstract: Democracy is one of the most contested words in the English language. In Africa, these complexities are compounded by the question of whether democracy is a colonial imposition. Cheeseman and Sishuwa provide a historiography of debates around democracy, track how these narratives have developed over time, and argue that there is widespread public support for a form of what they call "consensual democracy." This is not to say that democracy is universally loved, but despite the controversy it remains one of the most compelling ideals in political life, even in countries in which it is has yet to be realized.